Learning in response to workplace change - Tyler, Mark A. [Verfasser]; Choy, Sarojni [Verfasser]; Smith, Raymond [Verfasser]; Dymock, Darryl [Verfasser] (My University, 2014)
"Across the world, and particularly in developed countries, workplaces are changing, arguably more rapidly than ever before in response to external and internal forces. Altering the ways workplaces operate inevitably requires changes in the knowledge and skills workers need. This relationship is evident in the conclusion by the Australian Workforce and Productivity Agency (Future focus: 2013 National workforce development strategy, AWPA, Canberra, 2013) that the major influences on the nation's skills an workforce development needs are driven by globalization, technological change, the changing nature of work, the need to response to climate change impacts and issues of sustainability. These are very broad influences that raise questions about the extent to which they impact workers, as distinct from affecting industries and enterprises. […] That is, their need to learn as a result of workplace change is essentially based on maintaining their individual competence and hence their employability. This focus on their own workplace practice suggests that the most appropriate setting for individual learning in response to change appears to be the workplace itself, which in turn has implications for the way such learning is organized." Authors' abstract ; BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; L 2.1.1 Informelles Lernen; I 2.3.5 Australien, Ozeanien; Berufliche Weiterbildung; Technischer Wandel; Qualifikationswandel; Lebenslanges Lernen; Beschäftigungsfähigkeit; Lernen am Arbeitsplatz; Australien